Exploration of recovery of people living with severe mental illness (SMI) in low-income and middle-income countries (LMIC): A scoping review protocol - Gamieldien, F.; Galvaan, R.; Myers-Franchi, Bronwyn; Sorsdahl, K. (BMJ PUBLISHING GROUP, 2020)
Introduction: The construct of recovery was conceptualised in high-income countries and its applicability in low-income and middle- income countries is underexplored. A scoping review is proposed to synthesise knowledge, review conceptual overlap and map key elements of recovery from severe mental illness in low-income and middle-income countries. We aim to appraise the literature so as to inform future recovery-oriented services that consider the cultural and contextual influences on recovery from severe mental illness.